2019
DOI: 10.3390/bs9080084
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Motor Intervention Program on Motivation and Learning of English Vocabulary in Preschoolers: A Pilot Study

Abstract: (1) Background: Linking physical activity to the teaching of curricular contents provides numerous motivational and emotional benefits which improve academic performance and lead to the improvement and creation of healthy habits from an early age. (2) Method: The objective of the study is to analyze the effectiveness of a 5-week intervention program based on the use of a combined methodology of physical activity and gestures on motivation and vocabulary learning in English. The sample of children was aged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
10
0
3
Order By: Relevance
“…The validation of the data collection methods was reported in 12 studies (Bedard et al, 2017;Bedard et al, 2020;Callcott et al, 2015a;Duncan et al, 2019;Gao et al, 2019;Have et al, 2018;Lee et al, 2020;Pienaar et al, 2011;Sánchez-López et al, 2019;Shoval et al, 2018;Wen et al, 2018;Xiong et al, 2019a) and of these, only six studies (Callcott et al, 2015a;Gao et al, 2019;Lee et al, 2020;Pienaar et al, 2011;Wen et al, 2018;Xiong et al, 2019a) reported that the data collection methods demonstrated good reliability in that particular data. Most of the studies (Beck et al, 2016;Bedard et al, 2017;: Bedard et al, 2020;Botha and Africa, 2020;Ellemberg and St-Louis-Deschênes, 2010;Fischer et al, 2011;Fisher et al, 2011;Gao et al, 2019;Have et al, 2018;Habibi et al, 2014;Lee et al, 2020;Mavilidi et al, 2015;Mavilidi et al, 2016a;Mavilidi et al, 2017a;Mavilidi et al, 2018a;Padial-Ruz et al, 2019;Sánchez-López et al, 2019;St. Laurent et al, 2018;Xiong et al, 2017) reported both withdrawals and drop-outs in terms of numbers and reasons.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The validation of the data collection methods was reported in 12 studies (Bedard et al, 2017;Bedard et al, 2020;Callcott et al, 2015a;Duncan et al, 2019;Gao et al, 2019;Have et al, 2018;Lee et al, 2020;Pienaar et al, 2011;Sánchez-López et al, 2019;Shoval et al, 2018;Wen et al, 2018;Xiong et al, 2019a) and of these, only six studies (Callcott et al, 2015a;Gao et al, 2019;Lee et al, 2020;Pienaar et al, 2011;Wen et al, 2018;Xiong et al, 2019a) reported that the data collection methods demonstrated good reliability in that particular data. Most of the studies (Beck et al, 2016;Bedard et al, 2017;: Bedard et al, 2020;Botha and Africa, 2020;Ellemberg and St-Louis-Deschênes, 2010;Fischer et al, 2011;Fisher et al, 2011;Gao et al, 2019;Have et al, 2018;Habibi et al, 2014;Lee et al, 2020;Mavilidi et al, 2015;Mavilidi et al, 2016a;Mavilidi et al, 2017a;Mavilidi et al, 2018a;Padial-Ruz et al, 2019;Sánchez-López et al, 2019;St. Laurent et al, 2018;Xiong et al, 2017) reported both withdrawals and drop-outs in terms of numbers and reasons.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…For the studies assessing the learning of previously unknown items, i.e., where the baseline score was approximating zero (Padial-Ruz et al, 2019;Mavilidi et al, 2015;Mavilidi et al, 2016a;Mavilidi et al, 2017a;Mavilidi et al, 2018a;Toumpaniari et al, 2015), the effect sizes were calculated as:…”
Section: Effect Size Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Padial-Ruz et.al [15] examining the relation of physical activity to teaching content in children. Similar to a previous study by mavilidi [12], this study integrated gesture and physical activity to 88 children L2 learning.…”
Section: Resultsmentioning
confidence: 99%
“…Conceptual development is closely linked to motor development and experience; thus, the basis of learning experiences and the creation of meaning are based on sensory and motor participation (Volta & Volpe 2018). A number of the articles included in the present study which demonstrated the greatest acquisition of a foreign language, used programs based on multisensory activities (Ghisio et al, 2017) and motor activities such as songs and active tales, rhythmic activities (Campfield & Murphy, 2013;Hornickel & Kraus, 2013;Padial-Ruz et al, 2019), gestures, pantomimes or facial expressions (Kalivoda et al, 1971;Padial-Ruz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%